STRATEGI PENINGKATAN KUALITAS BELANJA DAERAH PROVINSI BANTEN - Satria, Yuki; Juanda, Bambang; Sarma, Mamun (Jurnal Manajemen Pembangunan Daerah, 2018)
The study aims to formulate an appropriate strategy for the Government of Banten Province in improving the quality of local expenditure. The study is conducted on the expenditure quality in Banten and then, continued to formulate the appropriate strategy for it. There are 12 indicators expenditures which are used. Expenditure discipline of allocation, the accuracy of the target in distributing grant and social financial support, the accuracy of schedule in determining APBD, the accuracy of schedule in realizing revenue and expenditure, the effectiveness and efficiency of expenditure accountability, transparency of local government financial report and BPK opinion on it. Data collection is done by distributing questioners, document analysis, and interviews. The results show that expenditure had been disciplined priority program, the allocation of capital expenditure is still low, the allocation of personnel expenditure is good, the grant and the social financial support had not reached target yet, there was still APBD which was determined unpunctually, unpunctually expenditure realization. The expenditure was not effective and efficient, there was still unaccountable, accountability has been transparency and BPK opinions has not good. The strategy to be implemented for this case is the increasing commitment of all sides to increase the expenditure quality of Banten Province region.Keywords: Strategy, Banten Province, Quality Of Spending, APBDPenelitian ini bertujuan untuk merumuskan strategi yang tepat bagi Pemerintah Provinsi Banten  dalam  meningkatkan kualitas belanja daerah.  Kajian dilakukan terhadap kondisi kualitas belanja dan dilanjutkan dengan penyusunan strategi. Ada 12 Indikator kualitas belanja yaitu disiplin belanja terhadap program prioritas, ketepatan alokasi belanja modal dan belanja pegawai, ketepatan sasaran pemberian hibah dan bansos, waktu penetapan APBD, realisasi pendapatan dan belanja, efektifitas dan efisiens, akuntabilitas, transparansi dan opini BPK. Pengumpulan data dilakukan dengan penyebaran kuesioner, analisis dokumen dan wawancara. Hasil penelitian yaitu belanja sudah disiplin dengan program prioritas, alokasi belanja modal masih rendah, alokasi belanja pegawai sudah baik, hibah dan bansos belum tepat sasaran, APBD belum tepat waktu, realisasi pendapatan tepat waktu, realisasi belanja belum tepat waktu, belanja belum efisien dan efektif, belanja belum semua dapat pertanggungjawaban, pertanggungawaban sudah transparan dan opini BPK belum baik. Strategi untuk diimplementasikan yaitu peningkatan komitmen seluruh pihak dalam rangka peningkatan kualitas belanja daerah Provinsi Banten.Kata Kunci : Strategi, Provinsi Banten, Kualitas Belanja, APBD